Electrophysiological Changes After Human Muscle Tear: A Potential Confounder. (July 2020) - Hearn, Sandra L.; Berri, Hassen M.; Little, Ann A.; Teener, James W.; Richardson, James K.
Abstract : Abstract: The goal of this prospective electrophysiologic study is to describe the chronological electromyographic findings observed in a human gastrocnemius muscle after a traumatic tear. A 30-yr-old man sustained a tear of the medial gastrocnemius. Needle electromyography was performed serially at 5, 15, and 26 wks after injury, with the contralateral gastrocnemius muscle serving as a control. Audiovisual recordings of the studies were analyzed in a blinded manner. Five weeks after injury, the affected gastrocnemius displayed increased insertional activity on electromyography. By 15-wk postinjury, insertional activity had diminished. However, motor unit action potentials showed chronic neurogenic morphological changes not previously observed. These changes persisted 26 wks after injury. The study findings reveal a chronological trajectory of increased insertional activity followed by reinnervation changes in a human muscle after local trauma, paralleling a course previously observed in a rat model. Electrodiagnosticians unaware of this phenomenon are at risk for making erroneous interpretations when examining patients with a history of muscle trauma.